1996
DOI: 10.1212/wnl.46.5.1376
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of postexercise facilitation and depression of motor evoked potentials to transcranial magnetic stimulation

Abstract: We studied the effects of exercise on motor evoked potentials (MEPs) to transcranial magnetic stimulation (TMS) and transcranial electrical stimulation (TES). Subjects performed 30-second periods of isometric exercise of the extensor carpi radialis until fatigue, which was defined as the inability to maintain half maximum force. The amplitude of MEPs to TMS recorded from the resting muscle after each exercise period was on average more than twice the pre-exercise value (postexercise MEP facilitation). After fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
139
3
2

Year Published

1997
1997
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 162 publications
(163 citation statements)
references
References 15 publications
19
139
3
2
Order By: Relevance
“…Such differences may explain the absence of post-exercise depression of MEPs in our present study. However, other investigators who have examined motor cortical excitability following`nonfatiguing' exercise (Brasil-Neto et al, 1993Samii et al, 1996Samii et al, , 1997 have identi®ed a transient period of facilitation immediately after completing the exercise. This facilitation ended after 4 min of rest, well short of the 15 min de®ned in the present study for the appearance of delayed facilitation of MEPs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Such differences may explain the absence of post-exercise depression of MEPs in our present study. However, other investigators who have examined motor cortical excitability following`nonfatiguing' exercise (Brasil-Neto et al, 1993Samii et al, 1996Samii et al, , 1997 have identi®ed a transient period of facilitation immediately after completing the exercise. This facilitation ended after 4 min of rest, well short of the 15 min de®ned in the present study for the appearance of delayed facilitation of MEPs.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were instructed to make this contraction with 20% of maximal force (since it has been demonstrated that from 10 to 50% of maximal contraction post-exercise facilitation does not change, Samii et al, 1996) and to imagine the¯exion of the index ®nger before initiating the movement. The level of the ongoing EMG activity during contraction was then monitored both by acoustic feedback and by asking the subjects to try and keep within a band displayed visually on a video screen.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations